Students’ Comprehension and Difficulties on Reading Descriptive Text at SMA Swasta Pencawan Medan - Herna Sianturi; Christina Siahaan; Syarifah Isma Dinda; Yenita Br Sembiring (Linguistic, English Education and Art (LEEA) Journal, 2020)
This research aims to find out the student's Reading Descriptive Text. The method used in this research is qualitative; the study was conducted at SMA Swasta Pencawan Medan with the samples were 30 students of XI MIA-2. The researcher used multiple-choice with ten questions, reading tests, and interviews. The data collected from the students' scores. The result showed that there is 0 student or 0 % who was categorized excellent, there were two students or 6,67% who were classified as very good, there were seven students or 23,3 % who categorized as good, there were seven students or 23,3% were categorized as fair, there were five students or 16,7 % who were classified unsatisfactory. There were nine students or 30 % who were categorized very poorly. So, from the result, the researcher can conclude that the students were still in the poor category. Keywords: reading, comprehension; reading comprehension problem; descriptive